Rhizoactinobacteria enhance growth and antioxidant activity in Thai jasmine Rice (Oryza sativa) KDML105 seedlings under salt stress - Chinachanta, Kawiporn; Shutsrirung, Arawan; Santasup, Choochad; Pathom-Aree, Wasu; Luu, Doan Trung; Herrmann, Laetitia; Lesueur, Didier; Prom-u-thai, Chanakan (MDPI, 2023)
Salinity is one of the most devastating abiotic stresses hampering the growth and production of rice. Nine indole-3-acetic acid (IAA)-producing salt-tolerant plant-growth-promoting rhizobacteria (ST-PGPR) were inoculated into Thai jasmine rice (Oryza sativa L.) variety Khao Dawk Mali 105 (KDML105) seedlings grown under different concentrations of NaCl (0, 50, 100, and 150 mM). The ST-PGPR strains significantly promoted the growth parameters, chlorophyll content, nutrient uptake (N, P, K, Ca, and Mg), antioxidant activity, and proline accumulation in the seedlings under both normal and saline conditions compared to the respective controls. The K+/Na+ ratio of the inoculated seedlings was much higher than that of the controls, indicating greater salt tolerance. The most salt-tolerant and IAA-producing strain, Sinomonas sp. ORF15-23, yielded the highest values for all the parameters, particularly at 50 mM NaCl. The percentage increases in these parameters relative to the controls ranged from >90% to 306%. Therefore, Sinomonas sp. ORF15-23 was considered a promising ST-PGPR to be developed as a bioinoculant for enhancing the growth, salt tolerance, and aroma of KDML105 rice in salt-affected areas. Environmentally friendly technologies such as ST-PGPR bioinoculants could also support the sustainability of KDML105 geographical indication (GI) products. However, the efficiency of Sinomonas sp. ORF15-23 should be evaluated under field conditions for its effect on rice nutrient uptake and growth, including the 2AP level.